2015
DOI: 10.1302/2046-3758.45.2000382
|View full text |Cite
|
Sign up to set email alerts
|

Biocompatibility of single-walled carbon nanotube composites for bone regeneration

Abstract: ObjectivesThe purpose of this study was to evaluate in vivo biocompatibility of novel single-walled carbon nanotubes (SWCNT)/poly(lactic-co-glycolic acid) (PLAGA) composites for applications in bone and tissue regeneration.MethodsA total of 60 Sprague-Dawley rats (125 g to 149 g) were implanted subcutaneously with SWCNT/PLAGA composites (10 mg SWCNT and 1gm PLAGA 12 mm diameter two-dimensional disks), and at two, four, eight and 12 weeks post-implantation were compared with control (Sham) and PLAGA (five rats … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(18 citation statements)
references
References 36 publications
1
17
0
Order By: Relevance
“…Results showed that MC3T3-E1 cells adhered, grew/survived and exhibited normal, non-stressed morphology and the addition of SWCNT strengthened cell proliferation rate and gene expression compared to pure PLAGA scaffolds. The authors further investigated the materials in vivo [195] and implanted composite materials into Sprague-Dawley rats for 2, 4,8 and 12 weeks of implantation time. Results showed that no mortality and clinical signs were observed.…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…Results showed that MC3T3-E1 cells adhered, grew/survived and exhibited normal, non-stressed morphology and the addition of SWCNT strengthened cell proliferation rate and gene expression compared to pure PLAGA scaffolds. The authors further investigated the materials in vivo [195] and implanted composite materials into Sprague-Dawley rats for 2, 4,8 and 12 weeks of implantation time. Results showed that no mortality and clinical signs were observed.…”
Section: Bone Tissue Engineeringmentioning
confidence: 99%
“…Composites of CNSs and biocompatible polymers can combine the properties of the two constituents and act as functional materials for a number of technological applications, [7,8] which include medical devices and implants [9][10][11][12], tissue engineering [13][14][15][16][17][18][19][20][21][22][23][24], drug delivery [25,26], bio-, green and wearable electronics [27][28][29], biosensing [29][30][31][32][33][34], soft robotics [35,36] and smart packaging [37][38][39].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Besides other applications, an effort has been applied to investigate the potential of carbon nanotubes, CNT, in biological and biomedical applications due to their "onedimensional" structure with high specific surface, stiffness, and electrical properties. Carbon nanotubes have been examined for potential application in bone and neural tissue engineering scaffolds, biosensors, drug and gene delivery as well as cell targeting and imaging [1][2][3][4][5] . Nevertheless, the use of CNT in biomedical applications has to be conducted with caution as pristine CNT was proved to be toxic and may be hazardous to human health.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the use of CNT in biomedical applications has to be conducted with caution as pristine CNT was proved to be toxic and may be hazardous to human health. However, the toxicity of CNT can be diminished by functionalization and further covalent modification, which has been investigated in several studies [2][3][4][5] . The length and shape of CNT, presence of catalyst residues, degree of carboxylation, covalent attachment of biomolecules and polymers as well as the dosage of CNT has been shown as important factors for their toxicity and safety [3,4,6] .…”
Section: Introductionmentioning
confidence: 99%